Advocacy to Reduce Malnutrition in Uganda: Some Lessons for Sub-Saharan Africa - Namugumya, Brenda Shenute (International Food Policy Research Institute, 2012)
There has been increasing recognition in Sub-Saharan Africa over the past decade of the significance of malnutrition as a brake on both human and economic development and a burden in the lives of many African households. Governments are taking measures to reduce the prevalence of malnutrition among their citizens, but the problem is serious: 57 million African children under five years of age suffer from chronic malnutrition, and 6 million of them are acutely malnourished (Black et al. 2008). More broadly, micronutrient deficiencies remain persistently high.